Slovenski pravični med narodi - Luthar, Oto; Šumi, Irena (ZRC SAZU, Založba ZRC, 2016)
To stand up against Nazi ideas of biologized "ethnicity" and antisemitism required a heroic disposition in individuals who did not allow themselves to have their basic humanity destroyed by such ideologies, even as the latter were backed by formidable political and religious power and sweepingly popular beliefs. The men and women presented in the first part of the book have already been recognised as Righteous Among Nations for their brave humanitarian acts during WWII, a title bestowed by the Yad Vashem World Center for Holocaust Research, Education, Documentation and Commemoration. Part Two brings the stories about people who were also saving Jews that were not recognised as Righteous yet, but some among them are candidates.